1995
DOI: 10.1037/0021-843x.104.1.94
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive function, cardiovascular reactivity, and behavior in boys at high risk for alcoholism.

Abstract: Boys (average age = 12.1 years) from families with an extensive history of paternal alcoholism differed from controls of similar age and IQ on measures of cognitive function, cardiovascular reactivity, and parent-rated conduct problems. High-risk boys performed most poorly on neuropsychological tests of frontal lobe function. According to tests of temporal organization and conditional-associate learning, control over working memory was the frontal subfunction primarily affected. A mental arithmetic task also e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
50
2
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 37 publications
4
50
2
1
Order By: Relevance
“…These findings suggest that alterations in physiologic responses to psychological stress may occur before heavy drinking begins. There are contrary findings of increased HR responses to mental arithmetic or threat of shock as stressors among boys and adolescents with a paternal history of alcoholism (Conrod et al, 1995;Harden and Pihl, 1995). The range of results at present suggests that additional work must be performed to determine whether differences in autonomic or endocrine reactivity to threatening conditions are genuinely associated with risk for alcoholism.…”
Section: Figcontrasting
confidence: 61%
“…These findings suggest that alterations in physiologic responses to psychological stress may occur before heavy drinking begins. There are contrary findings of increased HR responses to mental arithmetic or threat of shock as stressors among boys and adolescents with a paternal history of alcoholism (Conrod et al, 1995;Harden and Pihl, 1995). The range of results at present suggests that additional work must be performed to determine whether differences in autonomic or endocrine reactivity to threatening conditions are genuinely associated with risk for alcoholism.…”
Section: Figcontrasting
confidence: 61%
“…et al 1996;Harden & Pihl 1995;Pihl & Bruce 1995), and drug or alcohol use can cause neurocognitive deficits; trau matic brain injury can exacerbate both conditions. Using standardized neuropsychological tests, Meek and colleagues ( 1989) examined 34 male veterans entering residential sub stance abuse treatment and fo und deficits in attention, memory, calculation, abstraction, comprehension and visuo spatial abilities among 67% of the participants, although the mean scores were within normal ranges.…”
mentioning
confidence: 96%
“…In addition, frontal lobe dysfunction in male youth has been associated with pater nal alcoholism and can be evident even before the onset of alcohol use or brain injury, suggesting a developmental risk factor for substance use disorders (Giancola et al 1996;Harden & Pihl 1995;Pihl & Bruce 1995). Frontal lobe deficits are also associated with reductions in several cog nitive functions that are involved in moderating negative emotions (McAllister & Flashman 1999;Kaplan & Sadock 1998;Amen et al 1997) and solving problems-such as working memory (Goldman-Rakic 1998), temporal sequenc ing of tasks (Harden & Pihl 1995), and formulation of strategies (Hart, Scwartz & Mayer 1999; Shallice & Bur gess 1998)-as well as the incidence of depression and anxiety disorders (Hibbard et al 1998). Each of these defi cits presents important implications for clients in drug or alcohol abuse treatment.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…However, it is not the case that all males from this population or just multigenerational men show this effect: A further study differentiating individuals in terms of being low and high in histories of aggressive behaviour (assessed from ages 10 to 17 for physical aggression, destruction of property, and theft) showed that the high aggressives illustrated this effect when challenged as adults . Another characteristic is that even at an early age of 12 to 13 years, these at-risk individuals display relative deficits on cognitive tests, primarily measuring frontal lobe functioning (Harden & Pihl, 1995), deficits also found in at-risk individuals who show the response when of drinking age.…”
Section: The High Heart Rate Response To Alcohol Challengementioning
confidence: 99%